EFEKTIVITAS PROGRAM KELOMPOK WANITA TANI (KWT) DALAM UPAYA MENINGKATKAN PENDAPATAN RUMAH TANGGA DAN PEMBERDAYAAN EKONOMI MASYARAKAT: EFEKTIVITAS PROGRAM KELOMPOK WANITA TANI (KWT) DALAM UPAYA MENINGKATKAN PENDAPATAN RUMAH TANGGA DAN PEMBERDAYAAN EKONOMI MASYARAKAT - Rahyunanto, Setyo; Lestari, Retna Dewi; Winahyu, Nastiti; Pramudita, Willy (Universitas Duta Bangsa Surakarta, 2025)
The sustainability of a program activity implemented by a farmer institution is important to realize independence and improve knowledge, attitudes and skills with the aim of improving the economy of members and the community. The purpose of this study was to analyze the effectiveness of the women's farmer group program in an effort to increase household income and empower the community's economy. This study was conducted in Karanganyar District, Sragen Regency. Data collection techniques were carried out by observation, surveys and interviews. The population in this study was 30 women farmers with a sample of 30 women farmers taken using the sensus method. Data analysis used the effectiveness ratio. The results of the study showed that the effectiveness value of the indicators measured were 97% target accuracy, 100% socialization level, 97% program objectives and 73% program supervision. From this number, the average level of effectiveness of the farmer group program was obtained with a value of 91.75%.